The CAM Assay as an Alternative In Vivo Model for Drug Testing - Schneider-Stock, Regine; Ribatti, Domenico (Organotypic Models in Drug Development, 2021)
In the last decade, the chicken chorioallantoic membrane (CAM) assay has been re-discovered in cancer research to study the molecular mechanisms of anti-cancer drug effects. Literature about the CAM assay as an alternative in vivo cancer xenograft model according to the 3R principles has exploded in the last 3 years. Following a summary of the basic knowledge about the chicken embryo, we compare advantages and disadvantages with the classical mouse xenograft model, exemplify established and innovative imaging techniques that are used in the CAM model, and give examples of its successful utilization for studying major hallmarks of cancer such as angiogenesis, proliferation, invasion, and metastasis.
CRIS-Team Scopus Importer:2021-04-16
Keywords: 3R model; Angiogenesis; Anti-angiogenesis; CAM model; CAM xenografts; Chorioallantoic membrane; Drug delivery; In vivo model; Metastasis; Tumor growth